MODUL WEYL SEBAGAI REPRESENTASI GRUP SIMETRI DARI PEWARNAAN SUATU GRAF - Nisfulaila, Intan (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2022)
This research identifies the properties of Weyl module which had some similar properties with Specht module. Specht module as an irreducible representation of permutation module for some partition ???? of ???? has some contribution to determine the chromatic polynomial of bracelet graph with ???? colors. Due to the similarity, we had identify the application of the Weyl module properties as a representation of symmetric group of ???? colors in coloring bracelet graph so it can be used to determine the chromatic polynomial. The identification results show that although the determination of the dimensions of the Weyl module was similar to the determination of the dimensions of the Specht module, the results of the determination of these dimensions did not necessarily play a role in determining the number of coloring some graph.